The Influence of Training and Job Promotion on Employee Performance at PT. XYZ - Rahmadiani, Rani; Hasanuddin Hasanuddin; Jumawan Jumawan; Fauzi, Achmad; Setyawati, Novita Wahyu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research was conducted to analyze the effect of Training and Promotion on the Performance of Employees at PT. XYZ. This research uses a quantitative method with a sample size of 60 employees and employs a census sampling technique. The data collection technique used a questionnaire with several statements measured using a Likert Scale. Data analysis was conducted using the Structural Equation Modeling (SEM) method through SmartPLS 4.1 software. The research results show that partially, Training (X1) and Job Promotion (X2) have a significant positive effect on (Y) Employee Performance.